PERANAN INFORMASI AKUNTANSI MANAJEMEN DALAM PENGAMBILAN KEPUTUSAN PEMBELIAN BAHAN BAKU - Mulyadi Abdurrahman (Jurnal Akuntansi Muhammadiyah (JAM), 2010)
Management accounting information presented in very powerful company in purchasing raw materials. Raw materials can be used optimally in accordance with the criteria and in accordance with be existing data, the reports on the use of raw materials accounting period of the previous management. Inventories of raw materials can be compared to the use of which has been budgeted so that the production process can run continuously. Key words : information, accounting, management, raw material